The provenance of trans/gender: on the subject’s willful disappearance from the record - Wynholds, L. (Archival science, 2025)
In recent years, health and government information systems have made gender variance more visible and countable in the records. However, being counted has created novel forms of vulnerability for transgender and gender-diverse populations. This paper explores the complexity of records in exposing vulnerabilities of marginalization, illustrating how recordkeeping practices may contribute to erasure and stigma and reproduce systems of social disenfranchisement. The paper introduces the concept of ‘hostile recordkeeping practices’ as a critical analytical lens to articulate observations of marginalization in recordkeeping environments, to discuss indicators of bias, and to develop mechanisms for surfacing issues of trauma, violence, stigma, and repair. Using examples from the published literature, the paper discusses the importance of understanding social interactions which exacerbate marginalization within recordkeeping practices. Based on a case study, the paper argues that the dangers trans and gender-diverse individuals routinely encounter in recordkeeping practices necessitate additional analytical inquiry into hostile recordkeeping practices. The case study contributes to discussions of ethics of care for records for marginalized populations and includes interactional considerations, ethical considerations and historical contexts embedded in recordkeeping systems. The paper closes with an argument for the need to adapt existing recordkeeping practices to safeguard against hostile uses, systemic bias and structural violence. Future archival and medical discourses alike need to engage with the situation(s) of creation, the acts of recording, and, most importantly, personal agency in the negotiations of allowable uses for the records for marginalized populations.